Deteriora sequor. A neurophilosophical interpretation of the phenomenon of akrasia - Teruel, Pedro Jesús (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
Approaching the phenomenon of akrasia from the philosophical explanation of neuroscientific data delivers both theoretical and practical outputs. The neurophysiological foundation of the akratic actions belongs to the first ones, with the consequent increase of explicative capacity beyond the classic argumentation based on the notion of habit. Its therapeutic application to the fields of psychology and psychiatry belongs to the practical outputs. I propose therefore this approach as a theory with explicative and predictive value which achieves intertheoretical reduction and avoids ontological reductionism at the same time.